Cost-effectiveness of sacituzumab govitecan in hormone receptor-positive/human epidermal growth factor receptor 2-negative metastatic breast cancer - Shi, Demin; Li, Yan; Liang, Xueyan; Chen, Lingyuan (Frontiers in Oncology, 2023)
Background: The efficiency and safety of sacituzumab govitecan (SG) for the therapy of hormone receptor-positive (HR+)/human epidermal receptor 2-negative (HER2-) metastatic breast cancer (BC) have been demonstrated. The aim of this study is to evaluate its cost-effectiveness on HR+/HER2- metastatic BC from the third-party payer perspective in the United States. Methods: We performed the cost-effectiveness of SG and chemotherapy using a partitioned survival model. TROPiCS-02 provided clinical patients for this study. We evaluated the robustness of this study by one-way and probabilistic sensitivity analyses. Subgroup analyses were also conducted. The outcomes were costs, life-years, quality-adjusted life-years (QALYs), incremental cost-effectiveness ratio (ICER), incremental net health benefit (INHB), and incremental net monetary benefit (INMB). Results: SG treatment was related to an increase of 0.28 life years and 0.21 QALYs over chemotherapy, as well as a cost increase of $132,689, reaching an ICER of $612,772/QALY. The INHB was -0.668 QALYs, and the INMB was -$100,208. SG was not cost-effective at the willingness to pay (WTP) threshold of $150,000/QALY. The outcomes were sensitive to patient body weight and SG costs. SG may be cost-effective at the WTP threshold of $150,000/QALY if the price is less than $3.997/mg or the weight is under 19.88 kg. Based on the subgroup analysis, SG did not prove cost-effective in all subgroups at the WTP threshold of $150,000/QALY. Conclusion: From a third-party payer standpoint in the United States, SG was not cost-effective, even though it had a clinically significant advantage over chemotherapy for the treatment of HR+/HER2- metastatic BC. The cost-effectiveness of SG can be improved if the price is substantially reduced.